Synaptotagmin-IV Modulates Synaptic Function and LTP by Regulating BDNF Release - Dean, Camin (2009)
Synaptotagmin-IV (syt-IV) is a membrane trafficking protein that influences learning and memory, but its localization and role in synaptic function remain unclear. Here we discovered that syt-IV localizes to BDNF-containing vesicles in hippocampal neurons. Syt-IV/BDNF-harboring vesicles undergo exocytosis in both axons and dendrites, and syt-IV inhibits BDNF release at both sites. Knockout of syt-IV increases, and over-expression decreases, the rate of FM dye destaining from presynaptic terminals indirectly via changes in post-synaptic release of BDNF. Hence, post-synaptic syt-IV regulates the trans-synaptic action of BDNF to control presynaptic vesicle dynamics. Furthermore, selective loss of presynaptic syt-IV increased spontaneous quantal release, while loss of post-synaptic syt-IV increased quantal amplitude. Finally, syt-IV knockout mice exhibit enhanced LTP, which depends entirely on disinhibition of BDNF release. Thus, regulation of BDNF secretion by syt-IV emerges as a mechanism to maintain synaptic strength within a useful range during long-term potentiation.